Implementasi Prinsip Good Governance Dalam Pelayanan Pembuatan E-KTP Pada Kecamatan Sepatan Timur Kabupaten Tangerang - Marissa Krianayanti; Luthfiyyah Humairah; Anggita May Putri Kiswanto; Alodia Alvita Wibowo; Eko Prasetyo (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to gain a deeper understanding of the East Sepatan District's efforts in realizing excellent service in issuing E-KTP, which is based on the principles of good governance. Using a descriptive and qualitative approach, data was collected through field observations through interviews with informants consisting of Heads of Sections, Secretaries and Employees in East Sepatan District, as well as notes. Next, the data obtained was analyzed from the data reduction process, data presentation, and drawing conclusions. E-KTP services in East Sepatan District must meet the principles of good governance standards, namely including the principles of professionalism, transparency, supervision, responsiveness, democracy and participation, efficiency and effectiveness, foresight, and law enforcement, all of which comply with good governance standards. is trying to improve all these aspects and can be said to be almost on the verge of being good, but there are still several shortcomings and weaknesses in its implementation. The results of interviews and observations show that the e-KTP making service in East Sepatan District meets all the specified indicators. Solution So that good governance can be implemented optimally, governance principles such as legal regulations and justice need to always be considered and evaluated.